PENINGKATAN SKILL NARAPIDANA LEMBAGA PEMASYARAKATAN LOWOKWARU MALANG MELALUI KEGIATAN BUDIDAYA IKAN LELE DENGAN TEKNOLOGI RESRKULASI AKUAKULTUR SISTEM (RAS) DAN BUDIDAYA PAKAN ALAMI - Ramadhani, Putri; Irawan, Phobie Yolasica; Zahroh, Fathimatuz; Wahyudi, Moh. Ilham; Ghifari, Maulana Zaky; Handajani, Hany (Jurnal Abdi Insani, 2025)
Community service activities to improve the soft and hard skills of class 1 Malang prison inmates by striving for food independence through catfish cultivation with Recirculation Aquaculture System technology and natural feed cultivation. The activity is motivated by several problems, namely the difficulty of finding work for prisoners when leaving prison and officers cannot assist prisoners, lack of leisure activities and the lack of availability of animal protein. The program implementation methods include counseling, training and mentoring. The aim is to provide skills to prisoners and prison officers on fish farming RAS technology and natural feed. Utilize free time so as to increase productive time, and meet the animal protein needs of prisoners. The program method is carried out offline by starting with counseling and training activities, making racks and stocking Tubifex sp., cultivation of Daphnia sp. Making RAS technology, stocking catfish into tarpaulin ponds, monitoring, harvesting natural food, and harvesting catfish RAS technology system. Overall, this activity has good and satisfying results. The PKM PM team routinely provides assistance in the implementation of the service. This is known from the understanding of prisoners in implementing fish farming programs with recirculating aquaculture system (RAS) technology and natural feed cultivation in Malang Class 1 Correctional Institution, namely the maintenance of fish and natural feed Tubifex sp. and Daphnia sp. until the harvesting process and the fulfillment of animal protein for prisoners. As well as the realization of additional productive time for prisoners. So that the hope is that in the next three years the prisoners can continue the process of sustainable fish farming and natural feed cultivation. The program can be realized through 10 activities that have been carried out in the form of fish farming recirculation technology aquaculture systems and natural feed cultivation.